Floral finds on the territory of Kazakhstan - Пережогин, Ю.В.; Бородулина , О.В.; Ерохин, Н.Г.; Кубентаев, С.А. (Fundamental and Experimental Biology, 2023)
In the process of studying the Herbarium of the Institute of Plant and Animal Ecology (SVER), 16 plant species belonging to 12 genera from 10 families that were not previously noted for certain floristic regions (FR) of Kazakhstan were identified: Karatau FR – 2 species (Allium caeruleum and A. obliquum), Emben FR – 1 species (Allium strictum), South Ustyurt FR – 5 species (Alyssum dasycarpum, Amberboa nana, Amberboa turanica, Arnebia decumbens and Asparagus breslerianus) and Tobol-Ishim FR – 8 species (Bromus arvensis, B. squarrosus, Epilobium tetragonum, Matthiola superba, Psephellus sergii, Salix vinogradovii, Schoenoplectus hippolyti and Silene tatarica). Among the finds, Bromus arvensis is a new species for the flora of Kazakhstan. The results obtained significantly expand the existing understanding of the distribution of these species in the flora of Kazakhstan.